2022
DOI: 10.1039/d2cp02042d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of an α-synuclein NAC domain fragment with a ff14IDPSFF IDP-specific force field suggest β-sheet intermediate states of fibrillation

Abstract: Extensive MD simulations of the extended α-synuclein NAC domain fragment (35–97 residues) using ff14SB and ff14IDPSFF force fields lead to different conformational ensembles. The IDP-specific force field exhibits a potential β-sheet-rich intermediate state that could explain fibril formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“… 160 While ff14SB preserved the α-helices in α-synuclein, ff14IDPSFF predicted increased disorder and indicated the formation of β-sheet structures. 160 Other strategies involve adding CMAP corrections to both side chain and backbone dihedrals (RSFF2C 161 ) and adding corrections based on the chemical environment around a given aa (ESFF1 162 ). Rahman et al 142 found that the IDP-specific force fields obtain more reasonable results for pure IDPs.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“… 160 While ff14SB preserved the α-helices in α-synuclein, ff14IDPSFF predicted increased disorder and indicated the formation of β-sheet structures. 160 Other strategies involve adding CMAP corrections to both side chain and backbone dihedrals (RSFF2C 161 ) and adding corrections based on the chemical environment around a given aa (ESFF1 162 ). Rahman et al 142 found that the IDP-specific force fields obtain more reasonable results for pure IDPs.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…ff03CMAP is an example of another ff that works for both folded (in combination with TIP4P-Ew , ) and disordered proteins (in combination with TIP4P-D). Some other ff s like ff14IDPSFF , (modified from AMBER ff14SB) and CHARMM36IDPSFF , (modified from CHARMM36m) are CMAP-based and IDP-specific. The latter has been shown to reproduce the experimental conformational ensemble of multiple disordered proteins .…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 2 more Smart Citations